Prespective and Implementative of The Basis of The Single Prosecution System of The Prosecution of The Prosecution Bill - Priandhika Abadi Noer (Universitas Islam Lamongan, 2021)
Revision of Law no. 16 of 2004 concerning the Republic of Indonesia Attorney General's Office is a necessity because of the many changes that have occurred in the field. would replace Law no. 16 of 2004 is the right moment to encourage the Ago to do better.